NOISE IMMUNITY OF THE EQUIPMENT - Abdugafur Hotamov; Mirsaid Mirkomilov (Journals Park Publishing, 2023)
This article reflects that the concept of an overvoltage protection device differs from the concept of galvanic isolation in that when the protection is triggered, the current is diverted to the ground, and the electrical characteristics of the transmitted signal are distorted for the time of interference. Moreover, if the interference current diverted to the ground is large enough, then problems may arise in any other circuits due to communication through the total impedance or a surge in the potential of the earthing device.
Keywords: electrical strength, filters, galvanic separation.